Development of a New Amperometric Biosensor for Lactose Determination - Lourenço,R.J.M. (2003)
A new amperometric biosensor for lactose determinaion in raw milk was developed through the simultaneous immobilization of β-galactosidase and galactose oxidase on a derivatised polyethersulphone membrane. β-galactosidase catalyses the hydrolysis of lactose into galactose and glucose and galactose oxidase catalyses the oxidation of galactose into galactonic acid and H2O2. The membranes with the two immobilized enzymes were then used in an amperometric sensor, by oxidation of the H2O2 formed, at a Pt electrode of an Universal Sensors electrode base system. The sensitivity and the reproducibility of the biosensor thus formed were found to be 6.81 and 0.72 nA.M-1, respectively. Biosensors were found to be stable for 20 days.